Primal-Dual Fixed Point Algorithms Based on Adapted Metric for Distributed Optimization - Li, Huaqing; Zheng, Zuqing; Lu, Qingguo; Wang, Zheng; Gao, Lan; Wu, Guo-Cheng; Ji, Lianghao; Wang, Huiwei (IEEE transaction on neural networks and learning systems, 2023)
This article considers distributed optimization by a group of agents over an undirected network. The objective is to minimize the sum of a twice differentiable convex function and two possibly nonsmooth convex functions, one of which is composed of a bounded linear operator. A novel distributed primal-dual fixed point algorithm is proposed based on an adapted metric method, which exploits the second-order information of the differentiable convex function. Furthermore, by incorporating a randomized coordinate activation mechanism, we propose a randomized asynchronous iterative distributed algorithm that allows each agent to randomly and independently decide whether to perform an update or remain unchanged at each iteration, and thus alleviates the communication cost. Moreover, the proposed algorithms adopt nonidentical stepsizes to endow each agent with more independence. Numerical simulation results substantiate the feasibility of the proposed algorithms and the correctness of the theoretical results.